2014
DOI: 10.1902/jop.2014.130615
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Crown/Implant Ratio on Marginal Bone Loss: A Systematic Review

Abstract: Within the limitations of the present study, the C/I ratio of implant-supported restorations has an effect on peri-implant marginal bone level. Within the range of 0.6/1 to 2.36/1, the higher the C/I ratio, the less the peri-implant MBL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
76
1
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(95 citation statements)
references
References 33 publications
5
76
1
8
Order By: Relevance
“…The main reason for exclusion of articles was the fact that reporting of crown‐to‐implant ratio was not dealing with single‐tooth restorations (short implants were splinted to other short implants or splinted to longer implants) or data of single‐tooth restorations could not be extracted. Earlier systematic reviews on influence of crown‐to‐implant ratio (Blanes, 2009; Esfahrood et al., 2017; Garaicoa‐Pazmiño et al., 2014; Quaranta et al., 2014) included higher numbers of articles, but admitted that various restoration designs were present, with no distinction between splinted and nonsplinted crowns, making interpretation difficult. The authors of the present systematic review have the opinion that analyzing influence of crown‐to‐implant ratio should be done with single, nonsplinted, implant‐supported restorations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main reason for exclusion of articles was the fact that reporting of crown‐to‐implant ratio was not dealing with single‐tooth restorations (short implants were splinted to other short implants or splinted to longer implants) or data of single‐tooth restorations could not be extracted. Earlier systematic reviews on influence of crown‐to‐implant ratio (Blanes, 2009; Esfahrood et al., 2017; Garaicoa‐Pazmiño et al., 2014; Quaranta et al., 2014) included higher numbers of articles, but admitted that various restoration designs were present, with no distinction between splinted and nonsplinted crowns, making interpretation difficult. The authors of the present systematic review have the opinion that analyzing influence of crown‐to‐implant ratio should be done with single, nonsplinted, implant‐supported restorations.…”
Section: Discussionmentioning
confidence: 99%
“…Systematic reviews of Blanes (2009), Quaranta, Piemontese, Rappelli, Sammartino, and Procaccini (2014), and Esfahrood, Ahmadi, Karami, and Asghari (2017) revealed that high crown‐to‐implant ratios did not have an impact on peri‐implant bone loss; however, Garaicoa‐Pazmiño et al. (2014) reported as a result of their systematic review that the higher the crown‐to‐implant ratio the less the peri‐implant bone loss. In the systematic review of Blanes (2009), it was mentioned that there was no association between crown‐to‐implant ratio and technical complications, but, contrary, Quaranta et al.…”
Section: Introductionmentioning
confidence: 99%
“…Crown to implant ratio was evaluated in systematic reviews (Quaranta et al, 2014;Garaicoa-Pazmiño et al, 2014). A systematic review indicated that the prosthesist should provide careful planning with the implant-abutment interface when rehabilitating dental implants with unfavorable ratios C/I (Quaranta et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review indicated that the prosthesist should provide careful planning with the implant-abutment interface when rehabilitating dental implants with unfavorable ratios C/I (Quaranta et al, 2014). Garaicoa-Pazmiño et al (2014) stated that biomechanics and occlusal considerations are important factors; few clinical studies specified implant system used, opposing arch, and type of restoration. Our results indicated an increase in stress and strain on cortical bone under high crown implant (C/I) ratio; the implant screw was harmed with long crown, especially in oblique loading.…”
Section: Discussionmentioning
confidence: 99%
“…If the sleeve is detached, it is very difficult or impossible to refit to the base component. Moreover, desorption and floating of the zirconia sleeve from the titanium base can result in peri-implantitis 21,22) . Therefore, this bonding should be strong and stable for a long term.…”
Section: Discussionmentioning
confidence: 99%